Aberrant Synaptic PTEN in Symptomatic Alzheimer’s Patients May Link Synaptic Depression to Network Failure - Díaz González, Marta; Buberman, Assaf; Morales, Miguel; Ferrer, Isidro; Knafo, Shira (Frontiers in Synaptic Neuroscience, 2021)
In Alzheimer's disease (AD), Amyloid ß (Aß) impairs synaptic function by inhibiting long-term potentiation (LTP) and by facilitating long-term depression (LTD). There is now evidence from AD models that Aß provokes this shift towards synaptic depression by triggering the access to and accumulation of PTEN in the postsynaptic terminal of hippocampal neurons. Here we quantified the PTEN in 196,138 individual excitatory dentate gyrus syn-apses from AD patients at different stages of the disease and from controls with no neuropathological findings. We detected a gradual increase of synaptic PTEN in AD brains as the disease progresses, in conjunction with a significant decrease in synaptic density. The syn-apses that remain in symptomatic AD patients are more likely to be smaller and exhibit fewer AMPA receptors (AMPARs). Hence, a high Aß load appears to strongly compromise human hippocampal synapses, as reflected by an increase in PTEN, inducing a loss of AMPARs that may eventually provoke synaptic failure and loss.